Distribution and changes in mangrove area using satellite imagery of Landsat 8 OLI TIRS - Yunita, Nurul Fatimah; Usman, Muhammad; Merdekawati, Dewi; Maryono, Maryono; Januardy, Uray; Kristiandi, Kiki (JURNAL MINA SAINS, 2024)
Abstract This research aims to observe the distribution and changes in the area of mangrove vegetation in Jawai District, Sambas Regency, West Kalimantan Province. This sub-district is part of the administrative area of Sambas Regency and is one of 6 sub-districts that have coastal regions. The data used in this research is Landsat 8 satellite imagery, recording data from 2016 and 2022. The results of the data analysis show that of the total of 13 villages, only one village did not find mangrove vegetation in its area, namely Dungun Laut Village. Based on the analysis of the distribution of mangrove vegetation in 12 villages, there are two villages, namely Mutus Darussalam and Sarang Burung Danau, which show a decrease in the area of mangrove vegetation cover. Both experienced a reduction in the area of 0.184 ha and 42,081 ha, respectively. During 2016 and 2022, the lowest mangrove vegetation area was in Sentebang Village, 2,768 ha and 19,112 ha. The highest area of mangrove vegetation is increasing in Sarang Burung Kolam Village, with an area of 188,889 ha (2016) and 212,335 ha (2022). These findings show the importance of conservation in protecting the mangrove ecosystem in this area.